Penerapan Metode Drill and Practice untuk Meningkatkan Hasil Belajar Psikomotor Menjahit Saku Passepoille Berklep pada kelas XI SMKN 8 Surabaya - Arindy Tristantya Dewi; Ma’rifatun Nashikhah (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
This study aims to determine the increase in teacher and student activities, psychomotor learning outcomes, and student responses through the application of the drill and practice method in the practice of sewing a flapped pasepelle pocket fragment. This study was conducted at SMKN 8 Surabaya in the 2024/2025 academic year. The sample in this study were 32 students of class XI fashion 3. This type of research is a classroom action research (CAR) to determine the improvement of existing problems, by applying 4 stages of the cycle in the application of the drill and practice method in making a flapped pasepelle pocket fragment at SMKN 8 Surabaya. The data analysis technique used in this study is descriptive statistics. Data collection techniques in this study are using questionnaires, psychomotor tests, and observations. The results of the study prove that: 1) The application of the practice method in making a valved passemaklle pocket fragment obtained a final result with an average of 3.5 in cycle I and 3.7 in cycle II with a very good category index, 2) The application of the practice method in making a valved passemaklle pocket fragment was able to improve psychomotor learning outcomes with an average classical completeness of 53.1% in cycle I and became 78.1% in cycle II, with an increase of 25%. 3) The response of students in making a valved passemaklle pocket fragment by applying the practice method got a positive answer of 90.7% agreeing that the drill and practice method can improve skills with an average percentage of indicators of 76% with a good category. The findings of this study are that using the practice method (drill and practice) can improve the learning outcomes of class XI Clothing 3 students at SMKN 8 Surabaya on the material of making a valved passemaklle pocket fragment.